Anti-metastatic activity of Agrocybe aegerita galectin (AAL) in a mouse model of breast cancer lung metastasis. (February 2018) - Yang, Qing; Yin, Yalin; Pan, Yongfu; Ye, Xiangdong; Xu, Bo; Yu, Wenhui; Zeng, Haolong; Sun, Hui
Highlights: AAL preferentially accumulated in the lung of mice after tail vein injection. AAL exhibited anti-metastatic activity on a mouse model of 4T1 lung metastasis. The carbohydrates recognition determined the bioactivity of AAL. MMP-9 expression and activity were involved in the anti-metastatic effect of AAL. Abstract: Agrocybe aegerita galectin (AAL) has been reported to possess anti-tumor activity in tumor cells. The anti-metastasis activity of AAL in breast cancer and its possible mechanisms involved were investigated in this study. A bio-distribution assay showed AAL was highly absorbed by the lung. Administration of AAL (0.75 mg/kg twice or 1.5 mg/kg once) significantly inhibited pulmonary metastases of 4T1 cells and prolonged survival time of tumor-bearing mice. The binding between AAL and 4T1 cells relied on the carbohydrates recognition of AAL. AAL showed anti-proliferation activity against 4T1 cells with an IC50 of 4.11 M for 24 h treatment and 0.75 M for 48 h treatment. AAL induced apoptosis of 4T1 cells in a Caspase-3/7-dependent manner. Moreover, AAL inhibited migration and invasion of 4T1 cells, and decreased MMP 9 activity was found to be involved. This study would help to enhance the use of A. aegerita in nutritional and medicinal application.